EDUKASI MANFAAT EKSTRAK TEMULAWAK DAN JAHE SEBAGAI CAMILAN FUNGSIONAL IMUNOMODULATOR DI NAGARI SIPINANG PALEMBAYAN KABUPATEN AGAM - Syofyan; Aditio; Dwisari Dillasamola; Dwisari Dillasamola; Armenia Nazar; Fitri Rachmaini; Azya Hana Syakira; Rada Anjeli (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
Low public literacy regarding the utilization of medicinal plants as functional foods remains a challenge, particularly in rural areas. In fact, Curcuma xanthorrhiza (temulawak) and Zingiber officinale (ginger) contain bioactive compounds such as curcumin, gingerol, and shogaol, which have been proven to exert anti-inflammatory, antioxidant, and immunostimulant effects. This community service program aimed to improve public knowledge and skills in processing these two herbs into functional gummy candies that are more practical, palatable, and economically valuable. The program was conducted in May 2025 in Nagari Sipinang, Agam Regency, involving 40 participants ranging from productive-age adults to the elderly. A participatory approach was applied, including pre-test, interactive lectures, group discussions, hands-on gummy preparation, quizzes, post-test, and mentoring. Evaluation instruments consisted of knowledge questionnaires, interactive quizzes, and skill observations. Success indicators included increased health literacy, practical skills, and interest in product development. The results demonstrated a significant improvement in participants’ knowledge, from 40% before the intervention to 85% afterward. More than 80% of participants were able to explain the health benefits of temulawak and ginger, and actively engaged in the gummy preparation process. Enthusiasm was also reflected in the high participation rate during discussions and quizzes, along with the expressed interest in developing gummy products as potential local businesses. In conclusion, an integrated educational program combined with practical training effectively enhanced community health literacy and skills. The innovation of temulawak–ginger gummy not only supports immune health but also offers potential economic opportunities through locally based functional food products.